The environmental sustainability – assessment of regional priorities for air pollution reduction - Voytsekhovska, V. V.; Butzbach, O. (Publishing House of Lviv Polytechnic National University, 2016)
The problem of reducing air pollution as key element of environmental sustainability by regional criteria was considered. The basic study approach is taken, according to which the quantitative analysis methods were used to define the relation between air pollution reduction and the relative reduction volume of its negative impact on the region's inhabitants. The result proved that the product of two indicators – the concentration of air pollution and population density in the territory determines the priority of reducing pollution and as a result the implementation of regional eco investments. Conducted interpretation proposed approach using statistical data on air pollution for the largest cities in Italy and dust pollution areas for Polish Voivodships. Corresponding conclusions of practical significance and prospects of the proposed approach to the definition of regional priorities of reducing air pollution were made.
Keywords: environmental sustainability; regional development; air pollution reduction